2018
DOI: 10.1371/journal.pone.0191336
|View full text |Cite
|
Sign up to set email alerts
|

Association between temporomandibular disorders, chronic diseases, and ophthalmologic and otolaryngologic disorders in Korean adults: A cross-sectional study

Abstract: IntroductionTemporomandibular disorders (TMDs) are common musculoskeletal conditions in the maxillofacial area. Although strong relationships between TMDs and other pain and diseases exist, few studies have comprehensively assessed the association between chronic diseases, ophthalmologic and otolaryngologic disorders and TMD.MethodsOf 25,534 individuals included in the fifth Korea National Health and Nutrition Examination Survey (2010–2012), 17,575 aged ≥20 years who completed survey items on TMD symptoms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 50 publications
3
43
1
6
Order By: Relevance
“…The prevalence of TMD was higher in patients with tinnitus and hearing difficulty symptoms than in patients without tinnitus or hearing difficulty, which is consistent with previous TMD studies where reports of auditory complaints are common [35]. Moreover, patients with TMDs were at a greater risk of developing tinnitus and symptoms of a greater severity than patients without TMDs [40].…”
Section: Tinnitus Diagnosis and Complementary Testssupporting
confidence: 89%
See 3 more Smart Citations
“…The prevalence of TMD was higher in patients with tinnitus and hearing difficulty symptoms than in patients without tinnitus or hearing difficulty, which is consistent with previous TMD studies where reports of auditory complaints are common [35]. Moreover, patients with TMDs were at a greater risk of developing tinnitus and symptoms of a greater severity than patients without TMDs [40].…”
Section: Tinnitus Diagnosis and Complementary Testssupporting
confidence: 89%
“…TMD prevalence was found to be higher in patients with dizziness/balance disorder than in those without. Otologic complaints most frequently cited with TMDs in the study are dizziness, tinnitus, ear pain, ear fullness, and hearing loss [35]. de Moraes Marchiori et al reported that patients with TMDs are 2.38 times more likely to present with dizziness, and Chole et al conducted a case-control study to determine whether dizziness is more common in TMD patients compared to age-matched controls, finding dizziness to be significantly more prevalent in TMD group [3,45].…”
Section: Tinnitus Diagnosis and Complementary Testsmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, increasing evidence on the association between migraine and TMD may hinder the previous notion that those without TMD signs could have a migraine-related etiology. 7 We emphasized that 34 ears had anatomical abnormalities based on TMJ-MRI. The 34 ears with specific TMJ pathologies showed significant improvement in nonspecific EF after individualized TMJ treatment, suggesting a causative relationship between TMJ abnormalities on TMJ-MRI and nonspecific EF.…”
mentioning
confidence: 96%